Globalisasi di Negara Sekretif: VOA Burmese dan Demokrasi di Myanmar - Pratama, I Made Adhi (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 1 (2016), 2016)
ABSTRACT Democracy has successfuly promoted to international community through the process of Globalization. One of the process could be conducted through information transfer. International media known with its ability to set a certain agenda, while also enhance with the ability to multiply information. VOA Burmese as an international source of news intrinsively involved in spreading the value of democracy in one of the most secretive nation, Myanmar. Through the exposure of uncensored information, VOA Burmese has influenced the people of Myanmar on the issue of democracy and information transparency. Moreover, VOA Burmese has contributed in raising the awareness of democratric movement to the people of Myanmar. In this article, the author aims to describe the role of VOA Burmese in the democratization process of Myanmar, in 2000-2012. Kata kunci: VOA, Globalisasi, Myanmar, Demokrasi